Developments in surgical fluid therapy rates in veterinary medicine - Naden, Kristina (Veterinary Evidence, 2020)
PICO question Is there sufficient evidence to show surgical fluid therapy delivered at the recommended 3 mL/kg/hour for cats and 5 mL/kg/hour for dogs leads to a better outcome compared with widely accepted rates of 10 mL/kg/hour for both cats and dogs? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed Five studies were appraised. Two of these were opinion pieces, with one non-comparative prospective study, one randomised controlled trial, and one case control study. Strength of evidence Weak Outcomes reported Currently there is limited evidence to show that the surgical fluid therapy recommendations made by the 2013 Journal of the American Animal Hospital Association guidelines (Davis et al., 2013) for cats and dogs lead to a better outcome than accepted fluid therapy rates used. Fluid overload in humans can cause long-term adverse effects, however the same effects have yet to be shown specifically in veterinary patients Conclusion No evidence was found that provides strong, conclusive evidence that the 2013 recommendations by the American Animal Hospital Association and American Association of Feline Practitioners leads to a better outcome for both cats and dogs. The resulting research outlined below identifies a need to conduct clinical studies on the effects of fluid therapy on cats and dogs, and identify clear monitoring protocols to minimise and ideally avoid, fluid overload. When adequate, valid clinical studies have been carried out, this will provide sufficient information for the development of evidence-based recommended rates of fluid therapy for veterinary medicine, in a range of contexts How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision-making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.